Long-term financing - Childs, John Farnsworth (Englewood Cliffs, N.J. : Prentice-Hall, 1961)
The pros and cons of various types of financing questions are set down, and specific guides to the best course of action are given.
Includes index
ucj 15/01/2019
Loans
Keywords: Corporations- Finance; United States